2018
DOI: 10.1038/s41598-018-35281-y
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of an efficient in vitro propagation system for Iris sanguinea

Abstract: Iris sanguinea is a perennial flowering plant that is typically cultivated through seeds or bulbs. However, due to limitations in conventional propagation, an alternate regeneration system using seeds was developed. The protocol included optimization of sterilization, stratification and scarification methods as iris seeds exhibit physiological dormancy. In addition to chlorine-based disinfection, alkaline or heat treatment was used to break seed dormancy and reduce contamination. When seeds were soaked in wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…High concentrations of cytokinins have negative effects on shoot regeneration (Wang et al, 2018). We observed in our study that lower concentrations of BAP (2.0 mg/L or less) had the highest probability of regenerating shoots from all calli, with regeneration percentage and number of formed shoots greater than in higher concentrations (>2.0 mg/L).…”
Section: Discussionmentioning
confidence: 44%
“…High concentrations of cytokinins have negative effects on shoot regeneration (Wang et al, 2018). We observed in our study that lower concentrations of BAP (2.0 mg/L or less) had the highest probability of regenerating shoots from all calli, with regeneration percentage and number of formed shoots greater than in higher concentrations (>2.0 mg/L).…”
Section: Discussionmentioning
confidence: 44%
“…This could have resulted in a reduced tendency for shoot proliferation at high concentrations of BA (above 2.0 mg/l). Wang et al (2018) further indicated that an increase in cytokinin concentration above the optimal level negatively affects shoot regeneration. However, a study by Kurian and Thomas (2015) revealed that, contrary to our observation, a high concentration (2.0 mg/l) of BA was the most effective for Spilanthes acmella shoot proliferation from its nodal explants.…”
Section: Discussionmentioning
confidence: 98%
“…Direct multiple shoot induction is the appropriate method for plantlet propagation from mature trees with a lower risk of genetic variability compared to other regeneration methods, and it is a more reliable for clonal propagation [12][13][14][15] .…”
mentioning
confidence: 99%